2020
DOI: 10.21203/rs.3.rs-36637/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated analysis identifies a pathway-related competing endogenous RNA network in the progression of Pancreatic cancer

Abstract: Background: It is well acknowledged that cancer-related pathways play pivotal roles in the progression of pancreatic cancer (PC). Employing Integrated analysis, we aim to identify the pathway-related ceRNA network associated with PC progression.Methods: We divided eight GEO datasets into three groups according to their platform, and combined TCGA and GTEx databases as a group. Additionally, we screened out the differentially expressed genes (DEGs) and performed functional enrichment analysis in each group, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For instance, Zu et al found PVT1/miR-20b/ CCND1 ceRNA regulatory network associated with PC progression by comprehensive analysis. 22 Gao et al demonstrated that lncRNA DLEU1 promotes the development of PDAC through the miR-381/CXCR4 axis. 23 However, to our knowledge, a complete ncRNA-miRNA regulatory axis associated with CDK6 has not been established in PC to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zu et al found PVT1/miR-20b/ CCND1 ceRNA regulatory network associated with PC progression by comprehensive analysis. 22 Gao et al demonstrated that lncRNA DLEU1 promotes the development of PDAC through the miR-381/CXCR4 axis. 23 However, to our knowledge, a complete ncRNA-miRNA regulatory axis associated with CDK6 has not been established in PC to date.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one miRNA can be regulated by multiple LncRNAs and one mRNA can be targeted by several miRNAs in PC. For instance, Zu et al found PVT1/miR‐20b/CCND1 ceRNA regulatory network associated with PC progression by comprehensive analysis 22 . Gao et al demonstrated that lncRNA DLEU1 promotes the development of PDAC through the miR‐381/CXCR4 axis 23 .…”
Section: Discussionmentioning
confidence: 99%